IL-17 in the immunopathogenesis of spondyloarthritis - Taams, Leonie S; Steel, Kathryn J A; Srenathan, Ushani; Burns, Lachrissa A; Kirkham, Bruce W (Nature reviews. Rheumatology, 2018)
Spondyloarthritis (SpA) is a term that refers to a group of inflammatory diseases that includes psoriatic arthritis, axial SpA and nonradiographic axial SpA, reactive arthritis, enteropathic arthritis and undifferentiated SpA. The disease subtypes share clinical and immunological features, including joint inflammation (peripheral and axial skeleton); skin, gut and eye manifestations; and the absence of diagnostic autoantibodies (seronegative). The diseases also share genetic factors. The aetiology of SpA is still the subject of research by many groups worldwide. Evidence from genetic, experimental and clinical studies has accumulated to indicate a clear role for the IL-17 pathway in the pathogenesis of SpA. The IL-17 family consists of IL-17A, IL-17B, IL-17C, IL-17D, IL-17E and IL-17F, of which IL-17A is the best studied. IL-17A is a pro-inflammatory cytokine that also has the capacity to promote angiogenesis and osteoclastogenesis. Of the six family members, IL-17A has the strongest homology with IL-17F. In this Review, we discuss how IL-17A and IL-17F and their cellular sources might contribute to the immunopathology of SpA.